Slang Semantic Analysis on TikTok Social Media Generation Z - Syafaah, Lathifah Ayu; Haryanto, Sigit (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Language serves as a vital communication tool among individuals. There are various languages in the world, including Indonesian. Even so, each generation at its time will give birth to its own unique language style, and this also applies to the generation Z. This research aims to explore the semantic analysis of slang usage by Generation Z on social media. This research investigated: (1) the types of slang commonly used by Generation Z on social media, and (2) the reasons why Generation Z uses slang on social media. A qualitative descriptive method was employed to collect data from conversations on social media platforms, particularly TikTok, involving Generation Z. Data obtained through observations, documentation, and research questionnaires. Data analysis revealed that individuals, particularly Generation Z users, frequently employed slang on TikTok. The types of slang used include fresh and creative expressions, relaxed language styles, abbreviations, acronyms, and imitations of words. Based on observations, it is known that Generation Z uses slang on social media for various reasons, such as greeting friends or followers, starting conversations in a casual way, expressing impressions or feelings, and showing a sense of familiarity with their audience.